2015
DOI: 10.1038/cddis.2015.229
|View full text |Cite
|
Sign up to set email alerts
|

CD40 ligand induces RIP1-dependent, necroptosis-like cell death in low-grade serous but not serous borderline ovarian tumor cells

Abstract: Ovarian high-grade serous carcinomas (HGSCs) and invasive low-grade serous carcinomas (LGSCs) are considered to be distinct entities. In particular, LGSCs are thought to arise from non-invasive serous borderline ovarian tumors (SBOTs) and show poor responsiveness to conventional chemotherapy. The pro-apoptotic effects of CD40 ligand (CD40L) have been demonstrated in HGSC, though the underlying mechanisms are not fully understood. Conversely, the therapeutic potential of the CD40L-CD40 system has yet to be eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Our studies of cell death dependence on the caspase pathway and ROS generation showed that cell death induced by the potential synergistic effect of car–thy is independent of both pathways in all the cell lines treated, except for HL60, which shows a strong dependence on the caspase pathway. These results could partly explain the overexpression of Bax and CFLAR in this cell line following treatment and the inability of HL60 to express certain genes that may play a role in both apoptotic and nonapoptotic cell death pathways, such as CD40, TNF, TP53, ATF4, and ATP6V1G2 [ 32 , 33 , 34 , 35 ]. Cell death is often regulated by multiple molecular pathways and mechanisms, including apoptosis, autophagy, and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies of cell death dependence on the caspase pathway and ROS generation showed that cell death induced by the potential synergistic effect of car–thy is independent of both pathways in all the cell lines treated, except for HL60, which shows a strong dependence on the caspase pathway. These results could partly explain the overexpression of Bax and CFLAR in this cell line following treatment and the inability of HL60 to express certain genes that may play a role in both apoptotic and nonapoptotic cell death pathways, such as CD40, TNF, TP53, ATF4, and ATP6V1G2 [ 32 , 33 , 34 , 35 ]. Cell death is often regulated by multiple molecular pathways and mechanisms, including apoptosis, autophagy, and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 TNF-α is produced by microglia after a TBI 99,100 and correlates with TBI-induced hyperexcitability. 101 Additionally, upregulation of CD40L reportedly induces RIP1-dependent cell death, 102 and TNF-α blockade decreases CD40L levels 103 and CD40 activation. 104 This synergistic line of thinking is consistent with the significant linear relationship observed between RIP1, CD40L, and Iba1, and between PSVue 794 and Evans blue staining.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in allografts, expression of death receptor and necrosis related genes such as TNF, myelin-associated glycoprotein (MAG), Fas ligand (Fasl), cytochromes, and CD40 was upregulated beginning at day 1 and increasing until day 5 after transplantation (Supporting Information Fig. S1C) [38][39][40][41][42]. This was accompanied by a higher CD11c + DNGR-1 + DC infiltration of the allografts (BALB/c→C57BL/6) in comparison to syngrafts as demonstrated by double immunofluorescence staining ( Fig.…”
Section: Cell Necrosis In Cardiac Allografts Exposes Damps and Leads mentioning
confidence: 99%